2001
DOI: 10.1038/sj.ejhg.5200652
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 mutations among 233 unselected Finnish ovarian carcinoma patients

Abstract: Germline mutations of BRCA1 and BRCA2 predispose to hereditary breast-ovarian cancer syndrome. In Finland, 20 different BRCA1/2 mutations have been identified, and 13 of them are founder mutations that account for the vast majority of Finnish BRCA1/2 families. The purpose of our study was to determine the prevalence of BRCA1/2 mutations in unselected Finnish ovarian carcinoma patients and to evaluate the relationship between mutation carrier status and personal/family history of cancer. Two hundred and thirtyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 34 publications
4
36
1
Order By: Relevance
“…15 Of all BRCA1/2 mutations in Finland, the 999del5 appears to be the most common founder mutation, accounting for 17% of all BRCA1/2 families and one third of BRCA2 families. 12 In addition to Iceland and Finland, the BRCA2 999del5 mutation (reported as 995del5) has also been reported in one family of Puerto Rican origin 16 but, as yet, it…”
Section: ±13mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Of all BRCA1/2 mutations in Finland, the 999del5 appears to be the most common founder mutation, accounting for 17% of all BRCA1/2 families and one third of BRCA2 families. 12 In addition to Iceland and Finland, the BRCA2 999del5 mutation (reported as 995del5) has also been reported in one family of Puerto Rican origin 16 but, as yet, it…”
Section: ±13mentioning
confidence: 99%
“…Pedigree data was obtained from the Icelandic Genetic Council at the University Hospital of Iceland and verification of cancer diagnoses from the Department of Pathology, University Hospital of Iceland, and at the Icelandic Cancer Registry. Five of the families (2F, 4, 5A/ B, 6, and 7A/C) were large high risk families and 13 were pairs of sisters (2,10,13,15,16,21,23,24,32,51,57,59, and 67) diagnosed with breast cancer at the age of 60 years or younger. The Finnish 999del5 families were ascertained by four different research groups at the Helsinki, Tampere and Oulu University Hospitals by mutation screening of breast and breast-ovarian cancer families.…”
Section: Kindredsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19], but the data from the Danish population are much more limited. The largest study of BRCA1 and BRCA2 mutations to date from Denmark is the analysis of 103 multifocal or bilateral early-onset breast cancers, which identified mutations in 20% of cases (20).…”
mentioning
confidence: 99%
“…The highest frequencies have been shown among Ashkenazi Jews (35 and 27%; Boyd et al, 2000;Moslehi et al, 2000) compared to 4.7 and 3.5% in the Finnish (Sarantaus et al, 2001) and British population (Stratton et al, 1997), respectively. Previously, it has been reported that 3% of Norwegian ovarian cancers are caused by BRCA1 1675delA or 1135insA (Drum et al, 1999b).…”
Section: Discussionmentioning
confidence: 97%
“…After revision of the diagnoses, we had to omit 7% of the cases since they did not meet the criteria for ovarian cancer or borderline tumours. To date, relatively few studies on BRCA mutations are population based (Risch et al, 2001;Sarantaus et al, 2001). In most studies, women are selected on the basis of a family history positive for cancer, or for early age at onset.…”
Section: Discussionmentioning
confidence: 99%